FLUORINE IN BIRCH SAP AS AN INDICATOR OF FLUORITE ORE - Zamana L.V.; Leshnikov Yu.V. (My University, 1989)
The study of metal content of birch sap at several ore deposits has shown that such sap contains anomalously high concentrations of metals. The sensitivity of modern analysis makes it possible to determine some ore indicator elements directly in the raw sap, without going through the step of preliminary enrichment. Therefore, this method of biogeochemical exploration, given the widespread occurrence of birch in the tayga and forrest-steppe zones, has a high practical potential. The authors report on a study of fluorine contents in birch sap, designed to define the potential of this method in exploration for fluorite ore. The work was done at the Uluntuy quartz-fluorite deposit in eastern Transbaykal region and in a zone with the same geographical and geochemical properties, but with only background concentration of fluorine.